2020
DOI: 10.1002/er.6092
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on synthesis and characterization of biochars derived from lignocellulosic biomass for their candidacy in agronomy and energy applications

Abstract: Summary This study has dealt with the synthesis and characterization of biochars produced from three biomasses, viz. water hyacinth (whole plant and its components), yellow oleander, and sugarcane bagasse, and their comparative assessment for potential application in agronomy and energy production. The pyrolysis was carried out in a fixed batch reactor at 350°C and 550°C with a heating rate of 20°Cmin−1. Biochars were characterized for proximate and ultimate (elemental) analysis, and also using standard techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The measured surface area of a single-point BET was 200.4 m 2 /g and 246 m 2 /g for the ZIF-67 and pyrolyzed ZIF-67, respectively. The BET results also revealed that the potential of using MOFs above 500 °C enhanced the adsorption capacity of the films due to an increase in the surface area [ 48 ]. The Langmuir surface area was also enhanced by the pyrolysis of ZIF-67 because Langmuir surface area depends on the adsorption ability of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…The measured surface area of a single-point BET was 200.4 m 2 /g and 246 m 2 /g for the ZIF-67 and pyrolyzed ZIF-67, respectively. The BET results also revealed that the potential of using MOFs above 500 °C enhanced the adsorption capacity of the films due to an increase in the surface area [ 48 ]. The Langmuir surface area was also enhanced by the pyrolysis of ZIF-67 because Langmuir surface area depends on the adsorption ability of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar has diverse applications because of its unique properties, such as high carbon content, specific surface area, cation exchange capacity, nutrient retention capacity, and stable structure 76,77 . Based on these features, the biochar has been used as air, water, and soil decontamination, 78,79 additive in organic solid waste composting, 80 fuel alternatives, 81 catalyst, and support, 82,83 electrode, battery, and supercapacitor 84,85 …”
Section: Resultsmentioning
confidence: 99%
“…Biochar has diverse applications because of its unique properties, such as high carbon content, specific surface area, cation exchange capacity, nutrient retention capacity, and stable structure. 76,77 Based on these features, the biochar has been used as air, water, and soil decontamination, 78,79 additive in organic solid waste composting, 80 fuel alternatives, 81 catalyst, and support, 82,83 electrode, battery, and supercapacitor. 84,85 Investigating the functional groups on the biochar surface, measuring the surface area, and understanding the distribution of pore sizes are critical because many biochar applications rely on interactions occurring at the biochar surface.…”
Section: Bio-char Characterizationmentioning
confidence: 99%
“…Further studies assessing how branches, roots, and other components of the trees affect key biochar characteristics would be beneficial from the point of view of utilizing the whole biomass of hybrid aspen trees. Previously, Muigai et al [40] showed how different components of various plants can have varying nano-scale pore properties. Furthermore, previously also wood density has been suggested to affect pore properties [14].…”
Section: Impacts Of Clonal Differences and Within-tree Heterogeneitymentioning
confidence: 99%